The Utilization of Bagasse Natural Fiber to Make a Fiber Rope - Chairunnisa Ritonga; Saipul Bahri Daulay; Ainun Rohana (Universitas Sumatera Utara, 2014)
Bagasse is a byproduct of extraction (squeezing) of sugar cane. A single sugar mill can produces around 35-40% (weight) of bagasse from sugar cane milled. Bagasse which is a sugar cane mill waste can be processed into a fiber rope. Fiber rope can be made from many kind of tree bark, it makes the utilization of bagasse for a fiber rope is possible. The research was aimed to make a fiber rope from bagasse and to test the endurance of sugar cane fiber rope toward a tensile test.Results of the research indicated that each substance tested with the same weight produced different string diameter. Average value of examinatied 8 g streng had diameter of 5,83 mm, length of 58,3 mm, elongation of 22,66 mm, maximum loaded of 283,33 N, cross section of 2,489 x 10-5 m2, elongation at break of tensile strength of 105,6 x 105 N m-2, strain of 0,39, elasticity of 303,9 x 105 N m-2 and flexing of 38,7 %. Key Words: bagasse, fiber, rope, spun, tensile test.